The Role of International Political Institutions in the Integration Processes in the Eurasian Region - Vladimir Evgenyevich Frolov (Управленческое консультирование, 2018)
The article is devoted to studying the role of international political institutions in the integration processes of the Eurasian region. The author examines the Collective Security Treaty Organization, the Shanghai Cooperation Organization and the Organization for Democracy and Economic Development. The problem of duplication of integration associations of the Eurasian region is noted in the article. Also the author makes the conclusion that the experience of the Eurasian region in the sphere of military-political cooperation should be used in the process of formation of individual structures of the future Eurasian Union.